GOT2: a moonlighting enzyme at the crossroads of cancer metabolism and theranostics - Hu, Junxi; Liu, Qingwen; Ren, Qinglin; He, Wenbo; Hou, Jiaqi; Wang, Xiaolin; Shu, Yusheng (Frontiers in Immunology, 2025)
Moonlighting enzymes perform multiple distinct functions under different conditions without relying on gene fusion, splicing, or polymerization. Many classical metabolic enzymes, beyond their involvement in pathways like glycolysis and glutamine metabolism, also function as transcription factors, RNA-binding proteins, or signaling molecules. These dual roles are crucial in processes such as cancer metabolic reprogramming, immune evasion, and drug resistance. Glutamate oxaloacetate transaminase 2 (GOT2), a key example, is located in the mitochondria and catalyzes the transamination of aspartate and glutamate. Apart from its metabolic function, GOT2 also influences nuclear fatty acid metabolism and immune-related gene expression, affecting the tumor microenvironment. By integrating metabolic and signaling roles, GOT2 supports tumor cell adaptation to stress, promoting growth, survival, and immune escape. This multifunctionality positions GOT2 as a potential target for cancer diagnosis and therapy. This review discusses GOT2’s moonlighting roles and its clinical potential.